THE INFLUENCE OF ENGLISH TEACHERS’ EMOTIONAL INTELLIGENCE ON STUDENTS’ ENGLISH LEARNING AT MAN 1 KOTA GORONTALO: A QUALITATIVE STUDY - Fadlun Doda; Nonny Basalama; Moh Syahrun Ibrahim; Hasannudin Fatsah; Indri Wirahmi Bay; Asyraf Isyraqi Bin Jamil (Universitas Islam Negeri Sunan Gunung Djati, 2026)
This research investigates the effect of English teachers’ emotional intelligence (EI) on students’ English learning at MAN 1 Kota Gorontalo. Emotional intelligence, including the indicators such as self-awareness, self-regulation, motivation, empathy, and social skills, plays a crucial role in shaping classroom dynamics and fostering students’ motivation. The research aims to explore how English teachers’ EI influences students’ confidence, engagement, and enthusiasm in learning English. This research employed a qualitative case study design. The data were collected through semi-structured interviews and classroom observations involving two English teachers and ten students from grades 10 and 11 during the 2024/2025 academic year. Thematic analysis was used to identify key patterns emerging from participants’ experiences. Findings revealed that emotionally intelligent teachers significantly enhance students’ learning experiences through five major impacts: (1) enhancing self-confidence by appreciating efforts and normalizing mistakes; (2) creating supportive and enjoyable learning environments; (3) fostering intrinsic motivation through meaningful and engaging activities; (4) encouraging future aspirations such as studying abroad; and (5) providing emotional support and promoting peer collaboration. These practices contribute to a positive classroom climate where students feel valued, motivated, and resilient. The study concludes that teachers’ emotional intelligence is not only a personal quality but also a pedagogical competence essential for sustaining students’ motivation and well-being. It recommends integrating EI development into teacher training and professional programs to enhance both instructional effectiveness and emotional support in language education.